Fast parametrized biorthogonal transforms - Puchala, Dariusz; Yatsymirsyy, Mykhaylo (Видавництво Львівської політехніки, 2011)
W pracy zaproponowano schemat syntezy szybkich parametryzowanych przekształceń biortogonalnych oparty o diagramy przepływowe dla szybkich przekształceń ortonormalnych i dwupunktowe biortogonalne operatory motylkowe. In this paper the authors propose the technique ot synthesis of fast parametrised biorthogonal transforms that takes advantage of data-flow graphs for calculation of fast orthonormal transforms and two-point biorthogonal butterfly operators.
Keywords: szybkie parametryzowane przekształcenia liniowe; fast parametrised linear transforms